PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V SEKOLAH DASAR - Agil Nahar Febri Ema Tri Jida Maharani; Imaningtyas; Linda Zakiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop Augmented Reality (AR) learning media in Pancasila Education Subjects Class V Elementary School. This type of research is research and development with the procedure for the development stages using a 4D model (Define, Design, Develop, Disseminate). The results of the analysis of the validation of the assessment of material experts, media experts and linguists obtained an average product feasibility score of 96.66% in the very good category. In the one to one trial (3 users) got a score of 93.00% in the very good category. The small group trial (4 users) got a score of 94.00% with the very good category. And the field test (27 users) got a score of 94.00% with the very good category. The results of the product trial analysis data obtained an average feasibility score of 93.66% with the very good category. So that this Augmented Reality learning media video is suitable for use by students in learning, especially in the Pancasila Education subject class V Elementary School.